Parents' perceptions of antibiotic use and antibiotic resistance (PAUSE): a qualitative interview study. (16th March 2019) - Van Hecke, Oliver; Butler, Chris C; Wang, Kay; Tonkin-Crine, Sarah
Abstract: Background: There remains public misconception about antibiotic use and resistance. Preschool children are at particular risk of receiving unnecessary antibiotics because they commonly present in primary care and many childhood infections are self-limiting. Objectives: The aim of our study was to explore parents' perceptions and understanding of antibiotic use and resistance in the context of their young child with an acute respiratory tract infection (RTI) and to explore strategies parents would find acceptable to minimize antibiotic resistance for their families. Methods: Semi-structured interviews were conducted with 23 parents of preschool children who recently had an acute RTI across greater Oxfordshire, UK (2016–17 winter). We explored their beliefs about antibiotics, understanding of antibiotic resistance and views on current public antibiotic awareness campaigns at the time. Thematic analysis was used to analyse the data. Results: Parents had a sense of optimism and considered their families to be at low risk of antibiotic resistance because their families were 'low users' of antibiotics. Very few parents considered antibiotic resistance as a possible harm of antibiotics. Parents thought they were acting morally responsibly by following campaign messages. They wanted future campaigns to have a relevant, accessible message for families about the impact of antibiotic resistance. Conclusions: Future communication about the potential impact of unnecessary antibiotic use and antibiotic resistance needs to focus on outcomes that parents of young children can relate to (e.g. infection recurrence) and in a format that parents will engage with (e.g. face-to-face dissemination at playgroups and parent/child community events) to make a more informed decision about the risks and benefits of antibiotics for their child.